2022
DOI: 10.1590/0102-672020220002e1671
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Elastography in the Assessment of Reduction in Liver Steatosis and Fibrosis in the Early Postoperative Period After Bariatric Surgery

Abstract: BACKGROUND: Nonalcoholic hepatic steatosis is found in most obese patients and has a strong association with metabolic syndrome. The Roux-en-Y gastric bypass and the sleeve gastrectomy are the two techniques of bariatric surgery. Patients who underwent bariatric surgery have regression of nonalcoholic steatohepatitis due to a reduction in body mass index and changes in incretin hormones. AIMS: This study aimed to analyze the acuity of elastography in the regression of hepatic steatosis and fibrosis in obese p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Currently, bariatric surgery is the most effective weight-loss therapy, which plays a crucial role in the management of obese patients with NAFLD and NASH. Studies comparing liver biopsies before and after bariatric surgery have shown substantial improvements in liver histology, including fibrosis regression [5][6][7] .…”
Section: Mensagem Centralmentioning
confidence: 99%
“…Currently, bariatric surgery is the most effective weight-loss therapy, which plays a crucial role in the management of obese patients with NAFLD and NASH. Studies comparing liver biopsies before and after bariatric surgery have shown substantial improvements in liver histology, including fibrosis regression [5][6][7] .…”
Section: Mensagem Centralmentioning
confidence: 99%